Welcome to Limbo: literatura hispánica entre lugares - Mora, Vicente Luis (Diálogos Latinoamericanos, 2014)
In the late years many books of verses and novels published in Spain and Latin America included references to spaces between spaces. Places, Limbos or heterotopies (Foucault) characterized by temporary suspension in which the characters, or the poetic voice, think about the experience of lack of localization or consider the liquidity (Bauman) of the spatial experience in them. Beyond Auge’s concept of non-lieux, no longer useful for this kind of places between places, the text will try to explore the literary consequences of these new experiences, dividing them in limbic and aeronautic, looking forward to build an explanation of the high number of narrative and poetic uses in contemporary Transatlantic literature.